The origins of prescribed burning in Scandinavian forestry: the seminal role of Joel Wretlind in the management of fire-dependent forests - Cogos, Sarah; Roturier, Samuel; Östlund, Lars (European Journal of Forest Research, 2020)
International audience Abstract In Sweden, prescribed burning was trialed as early as the 1890s for forest regeneration purposes. However, the origins of prescribed burning in Sweden are commonly attributed to Joel Efraim Wretlind, forest manager in the State Forest district of Malå, Västerbotten County, from 1920 to 1952. To more fully understand the role he played in the development of prescribed burning and the extent of his burning, we examined historical records from the State Forest Company’s archive and Wretlind’s personal archive. The data showed that at least 11,208 ha was burned through prescribed burning between 1921 and 1970, representing 18.7% of the Malå state-owned forest area. Wretlind thus created a new forestry-driven fire regime, reaching, during peak years, extents close to historical fire regimes before the fire suppression era, and much higher than present-day burning. His use of prescribed fire to regenerate forests served as a guide for many other forest managers, spreading to all of northern Sweden during the 1950–1960s. Our analysis of Wretlind’s latest accounts also shows how he stood against the evolutions of modern forestry to defend a forestry system based on the reproduction of natural processes, such as fire.